Long‐ and short‐distance signaling in the regulation of lateral plant growth - Brackmann, Klaus; Greb, Thomas (Physiologia plantarum, 2014)
Lateral growth of shoot and root axes by the formation of secondary vascular tissues is an instructive example for the plasticity of plant growth processes.
Gesehen am 17.02.2017